Effects of immersive virtual therapy on psychological and physical wellbeing in women with breast cancer at different stages of disease and treatment conditions: an experimental comparative study - Czech, Oliver; Matkowski, Rafal; Skórniak, Jakub; Malicka, Iwona (Frontiers in Oncology, 2025)
BackgroundBreast cancer (BC) is the most common cancer worldwide, with rising incidence and complex treatment challanges. Patients often experience physical and psychological symptoms that negatively affect their quality of life. Virtual Reality (VR) has shown promise as a supportive, non-pharmacological intervention by reducing anxiety, depression, pain and aiding physical rehabilitation in cancer care.ObjectiveThis study evaluated the impact of immersive VR therapy in improving the psychological and physical wellbeing of women with BC at different stages of treatment and compared outcomes across treatment groups.MethodsFifty-six women were recruited at the Lower Silesian Oncology, Pulmonology and Hematology Center in Wroclaw, Poland, and divided into four equal groups (n = 14) based on their treatment stage: recently diagnosed before treatment (diagnosis group), in the perioperative period (surgery group), undergoing radiotherapy (radiotherapy group), and post-treatment (healed group). All participants completed ten VR therapy sessions involving therapeutic tasks in a virtual garden. Outcome measures included anxiety (State-Trait Anxiety Inventory), depression (Beck Depression Inventory), coping strategies (Mini-Mental Adjustment to Cancer), physical activity (International Physical Activity Questionnaire), and sleep quality (Pittsburgh Sleep Quality Index). Repeated measures ANOVA was used to) assess changes over time.ResultsAnxiety (F = 15.82, ηp² = 0.23, p < 0.001), depression (F = 32.48, ηp² = 0.38, p < 0.001), coping strategies (F = 4.78, ηp² = 0.08, p = 0.03), physical activity (F = 6.48, ηp² = 0.11, p = 0.01, and F = 6.97, ηp² = 0.12, p = 0.01), and sleep quality (F = 9.36, ηp² = 0.15, p < 0.01) improved significantly. However, no significant differences were found between treatment groups.ConclusionsImmersive VR therapy effectively supports both mental and physical wellbeing in woman with BC, regardless of treatment stage. These findings suggest VR is a versatile and valuable tool for supportive care in oncology. Future studies should explore it’s use in broader clinical settings, including outpatient and home-based care.